What kind of intuition for what kind of education: A scoping review - Rosa Cera; Marta Sinclair (Encyclopaideia)
The general purpose of this scoping review is to investigate the role of intuition in Higher Education. In particular, it aims to understand the contribution of intuition to achieving disciplinary objectives. The review method used is that of Arksey and O’Malley, of a qualitative type, the data were extracted in an “analytical-descriptive” mode, in order to detect the profound meaning of the content present in the reviewed articles. The qualitative-interpretative approach and the thematic analysis of relevant parts of text have made it possible to grasp the essence of educating by means of intuition. ERIC, Education Source Ultimate, Scopus, Web of Science, APA PsycArticles are the electronic databases consulted, 2020-2024 are the years considered. The results show that STEM disciplines are more interested in the educational dimension of intuition and conceptualise it according to psychological or neurological theories; they find it useful in experiential learning for training expert intuition through visual elements. The disciplines related to humanities prefer, however, to train creative intuition, imbued with emotions, through readings and discussions in a small group.